Encryption as the cornerstone of big data security. Issue 3 (March 2017) - Tankard, Colin
Abstract : Big data refers to huge data sets that have come about through the phenomenal growth being seen in the volume of information collected, produced, analysed, shared and stored by organisations. By analysing big data sets, valuable insights can be gained into how patterns of data are associated to enable better-informed decision-making, which can aid in competitiveness and drive innovation. According to Gartner, 48% of organisations had invested in big data capabilities in 2016. Big data programmes benefit organisations in many ways, driving competitiveness and innovation. But they can also increase security risks owing to the vast amount of sensitive information they hold. Big data sets harness information from multiple sources such as databases, data warehouses, log and event files, security controls such as intrusion prevention systems and usergenerated data from sources such as emails and social media posts. So data security is a must for any organisation, and encryption needs to be a key part of that, says Colin Tankard of Digital Pathways.